Short Communication: Investigation of leaf architectural patterns: Implications in delineating taxonomically controversial Hoya merrillii Schlechter and Hoya quinquenervia Warburg - DIANA P PAGUNTALAN; INOCENCIO E BUOT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Paguntalan DP, Buot JrIE. 2019. Short Communication: Investigation of leaf architectural patterns: Implications in delineating taxonomically controversial Hoya merrillii Schlechter and Hoya quinquenervia Warburg. Biodiversitas 20: 833-839.  Variations in leaf traits of two very likely similar plants, Hoya merrillii Schlechter and Hoya quinquenervia Warburg were examined together with an outgroup, Hoya cagayanensis Burton. The objectives of the study are to examine the leaf architectural characteristics of Hoya merrillii and Hoya quinquenervia and use the information as an additional basis of delineation between the said species of Hoya plants. Thirty leaf samples for each species were examined for laminal and vein characters. The characters laminar size, laminar shape, number of basal veins, quinternary vein fabric, areole development and characteristics of FEVs (free-ending veins), were well-defined from either one or both species. Overall, the results showed variability between the studied plant groups using univariate and multivariate analysis. The data ordination on the morphometric traits using PCOa showed distinct groupings among studied leaf samples and yielded consistent results with the single linkage or nearest neighbor cluster dendrogram which showed distinct clustering of individual species in terms of morphometric traits that were considered in the study. Detected variations of the leaf architectural traits on the leaves of Hoya merrillii Schlechter and Hoya quinquenervia Warburg allowed for the more available basis of separation in addition to established floral morphologies that are primarily used as criteria for delineation between species. Variations in leaf architecture characters can be of great value to illustrate or imply meanings in the taxonomic relationships of the Hoya species studied.